Micromechanical analysis of the rutting evolution of asphalt pavement under temperature–stress coupling based on the discrete element method. (28th March 2022) - Zhang, Xia; Chen, Enli; Li, Nanpeng; Wang, Lianfang; Si, Chundi; Wang, Cuiyan
Highlights: Mechanical relationships between macro- and microparameters were deduced. Rutting simulation and test of Hamburg pavement was conducted. Burgers parameters of asphalt at different temperatures were Obtained by creep tests. Distribution and transmission mechanism of contact force in rutting were revealed. Abstract: The macrorutting phenomenon of asphalt pavement is intrinsically related to the micromechanical characteristics of asphalt mixtures. In addition, changes in temperature and the repeated action of vehicles keep the pavement in a complex service state. Based on the discrete element method, this paper conducted a virtual rutting test of Hamburg pavement to capture the micromechanical evolution mechanism of rutting under complex temperature–stress coupling. Burgers and linear constitutive models were adopted to describe the viscoelastic and linear properties of mastic and aggregates, respectively. The transformation relationships between macro- and microparameters were deduced based on mechanical theory, and the macroparameters at different temperatures were determined through a creep test. To improve the calculation efficiency, the static load equivalent and time temperature equivalent principles were adopted to simulate pavement rutting, which was verified by laboratory rutting tests. In addition, the movements of coarse aggregates and the contact forces within the mixture were statistically analyzed under different loading times, temperatures and tire pressures. The results showed that the virtual rutting test can accurately predict the permanent deformation of pavement under a complex temperature–stress coupling field. The mechanical response analysis demonstrated the load distribution and transfer mechanism within the pavement and clearly explained the evolution process of rutting from the perspective of micromechanical views. Moreover, the influence law of parameters on rutting performance was illustrated using micro discrete mechanical theory.